Management of Urolithiasis in Cat with Special Diets - Steven Taufic Leo; Lita Rakhma Yustinasari; Juliano Mwenda Ntoruru (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: The current study is focused on the treatment of a cat with urolithiasis. The main goal is tohelp provide a greater understanding of how to treat the cat with special diets.Case Description: Struvite urolithiasis was found in a 3-year-old female domestic short-haired cat withthe complaint of straining for a week during urination. Ultrasonographs indicated the existence of twocalculi in the bladder that were also detected by radiographic examination (7 mm in diameter each). Bladderstones were getting smaller by dissolution diets therapy. In this case, the cat was treated by melox 1.5 mg/ml (dosage 0.1 mg/kgBW) for 14 days, tramadol for 28 days (2mg/kg BW) and also special diets (struvite).Conclusion: After a month treatment,the stones were almost cannot be seen radiographically. This reportdescribes a cat with urolithiasis case which was successfully treated with special diets for struvite withoutany surgery.